Media technology and society : a history : from the telegraph to the Internet - Winston, Brian (Routledge, 1998)
How are new media born? How do they change? And how do they change us? This work reports on the history of communication technologies, from the printing press to the Internet, and seeks to challenge the myth of an 'information revolution'.